2020
DOI: 10.1039/c9ta12605h
|View full text |Cite
|
Sign up to set email alerts
|

A chlorinated nonacyclic carbazole-based acceptor affords over 15% efficiency in organic solar cells

Abstract: A systematic approach involving conjugation extension and end group chlorination is capable of enhancing both JSC and PCE. Overall, the PM6:DTTC-4Cl-based device delivers a remarkable PCE of 15.42% with a VOC of 0.92 V, a JSC of 22.64 mA cm−2 and an FF of 74.04%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…[ 42 ] Furthermore, Hsu and co‐workers replaced the fluorine atoms by chlorine atoms in 4TCIC‐4F to develop a new carbazole‐based acceptor DTTC‐4Cl and obtained an outstanding PCE of 15.42% as blending with PM6. [ 43 ] These results demonstrated that carbazole‐based SMAs have great application potential in OSCs. For 4TCIC‐4F, there are two types of side chains ( Figure a), the four alkylphenyl side chains are appended to the two sp 3 hybridized carbon atoms, and the branched 1‐octylnonyl (C8C8) side chain is appended to the sp 2 hybridized nitrogen atom in the carbazole unit.…”
Section: Introductionmentioning
confidence: 89%
“…[ 42 ] Furthermore, Hsu and co‐workers replaced the fluorine atoms by chlorine atoms in 4TCIC‐4F to develop a new carbazole‐based acceptor DTTC‐4Cl and obtained an outstanding PCE of 15.42% as blending with PM6. [ 43 ] These results demonstrated that carbazole‐based SMAs have great application potential in OSCs. For 4TCIC‐4F, there are two types of side chains ( Figure a), the four alkylphenyl side chains are appended to the two sp 3 hybridized carbon atoms, and the branched 1‐octylnonyl (C8C8) side chain is appended to the sp 2 hybridized nitrogen atom in the carbazole unit.…”
Section: Introductionmentioning
confidence: 89%
“…Chen et al [56] reported the synthesis of a novel NFA b11 with a carbazole moiety instead of a benzene ring, combined with a chlorine-substituted end-capping group. The carbazole moiety has a strong electron-donating capacity, and, consequently, the resulting core is richer in terms of electron density.…”
Section: Structural Modification Of the Idic/itic Corementioning
confidence: 99%
“…In recent years, bulk heterojunction (BHJ) polymer solar cells (PSCs) are steadily and rapidly developing with power conversion efficiencies (PCEs) over 18 % [1][2][3][4][5][6][7][8][9][10] due to the continuous optimization of the molecular structure of materials, [11][12][13] the configuration and fabrication process of photovoltaic devices. [14][15][16] This outstanding achievement is mainly ascribed to the fact that fullerene-based acceptors were substituted by the springing up of new nonfullerene small-molecule acceptors (SMAs) thanking to their superior optical absorption properties, easily tunable molecular energy levels, and potential for relatively low-cost production processes.…”
Section: Introductionmentioning
confidence: 99%